2017
DOI: 10.1108/apjml-10-2015-0154
|View full text |Cite
|
Sign up to set email alerts
|

The influence of perceived social media marketing activities on brand loyalty

Abstract: Purpose The purpose of this paper is to investigate the impact of social media marketing activities on brand loyalty, value consciousness and brand consciousness. Design/methodology/approach A self-administered questionnaire was developed and administered to a convenience sample of 346 undergraduate students Findings The findings of this research indicated that social media marketing has a significant effect on brand loyalty; brand consciousness and value consciousness mediate the relationship between soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
248
5
45

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(324 citation statements)
references
References 70 publications
26
248
5
45
Order By: Relevance
“…The tenth and last article in this special issue by (Ismail, 2017) this study confirmed the growing importance of social media marketing. It also provided insights for marketers on envisioning brand loyalty.…”
Section: Articles In This Special Issuesupporting
confidence: 63%
“…The tenth and last article in this special issue by (Ismail, 2017) this study confirmed the growing importance of social media marketing. It also provided insights for marketers on envisioning brand loyalty.…”
Section: Articles In This Special Issuesupporting
confidence: 63%
“…The same is mentioned in the study of Grubor et al (2017) which states that firm created social media communication positively and significantly influence toward behavioral loyalty. Perceptions of social media marketing activities are the main drivers of brand loyalty because followers of brand pages in social media tend to be loyal and committed to brands (Ismail, 2017). In the study, the positive effect indicates that the better the evaluation of firm created content created in Emina Cosmetic official social media, the higher the consumer loyalty to the Emina Cosmetic brand.…”
Section: Test Results Influence Evaluation Firm Created Content and Usmentioning
confidence: 70%
“…Previous studies have discussed the effect of social media marketing on brand loyalty, and the mediating effect of value consciousness and brand consciousness on the relationship between social media marketing and brand loyalty. This study tests the model (Ismail, 2017) in the context of Saudi Arabia, and developed a conceptual model that relates further, the variables, brand loyalty to eWOM, eWOM to purchase intentions, and perceived social media marketing to purchase intentions. Although the topic is discussed in literature, there is lack of research among the variables discussed.…”
Section: Importance Of the Studymentioning
confidence: 99%
“…Brand consciousness is defined as a concept that brand names are important in the psychological prepurchase process, (Nelson & McLeod, 2005;LaChance et al, 2003) the process that precedes the buying act. Despite its importance, the impact of perceived social media marketing activities on brand consciousness remains relatively unknown (Ismail, 2017). As brand information is shared at low costs among firms, consumers, and their peers, this increases brand awareness, brand loyalty and enhances brand recognition (Gunelius, 2011).…”
Section: Brand Consciousnessmentioning
confidence: 99%
See 1 more Smart Citation